TRANSMISSION MECHANISM OF MONETARY POLICY IN NIGERIA (2011)
The Central Bank of Nigeria (CBN) has pursued among other goals, low and stable domestic price level and output growth using various monetary policy instruments. Despite these efforts, output growth rate averaged 1.32% between 1980 and 1989 and 2.87% between 1990 and 1999. Also, the monetary authority’s inflation rate target of 5.00% in 1992 and 31.00% in 1995 escalated to 44.59% and 72.81% respectively. There has been limited attempt to investigate the channels through which monetary policy affects output and prices in Nigeria. This study, therefore, empirically investigated monetary policy transmission mechanism and sought to establish the relative effectiveness of various monetary policy instruments in Nigeria. A Monetary Transmission Mechanism (MTM), predicated on Mishkin framework, that captures the impact of monetary policy in an economy was employed. The MTM focused on bank lending, exchange rate and interest rate channels, evident in most developing economies like Nigeria. A Structural Vector Autoregressive (SVAR) model, based on monetary policy transmission dynamics which identified the magnitude and impact of structural shocks, was developed to test the importance of these channels. Generic, composite and separate models including the impulse responses of the channels were estimated. Variance decomposition was also conducted to determine the magnitude of fluctuation attributable to different shocks. With quarterly data from 1970 to 2008, the time series properties of the models’ variables were ascertained using the Augmented Dickey-Fuller and Phillips-Perron tests. The effectiveness of Reserve Money (RM) as a monetary policy instrument over Interest Rate (IR) was evident as a marginal increase of 0.15% in RM precipitated increased output and prices declined by 0.20% and 0.60% respectively. The weakness of IR as a policy instrument was shown with an increase of 2.02% in IR yielding no significant response from output and prices. Bank lending declined from 0.89% in the first quarter to 0.23% below the baseline in the second quarter following a marginal increase of 0.05% in RM. Output declined consequently below the baseline by 0.12% and 0.15% while prices rose by 0.15% and 0.10% in the second and third quarters respectively. By implication, the weak response of exchange rate to similar increases in IR of 2.02% and RM of 0.15% suggested that this channel did not capture MTM in Nigeria. Also, output and prices’ non-response to increase in IR of 2.02% and RM of 0.15% suggested that interest rate channel was weak. Bank lending channel remained the existing MTM in Nigeria, while the impact of monetary policy shock on output and prices occurred only after a time-lag of six years. Reserve Money was a potent policy instrument with output responding more to policy variations than prices. Bank lending remained a significant channel for propagating policies to target variables. The CBN should therefore focus more on the use of RM as a policy instrument rather than a hybrid of RM and IR. There should also be emphasis on price level stability since this has the tendency of fostering output growth.